Differences in Mathematic Connection Abilities and Self-Efficacy between Students Given Approaches Realistic Mathematics with the Approach Inquiry at Senior High School 2 Tanjung Morawa - Khairina Hazrati; Ani Minarni; W. Rajagukguk (BIRCU, 2020)
This study aims to determine how the difference between mathematical connections and self-efficacy between students who are given a realistic mathematics approach with an inquiry approach at Senior High School 2 Tanjung Morawa. The sample used in this study was Senior High School 2 Tanjung Morawa. With the method of collecting literature study data. The method used is literature study. The results of this study indicate that the overall approach to mathematics is realistic and inquiry, each of which has advantages and disadvantages, but in this study a good approach to use in students' ability to solve math problems is the inquiry approach, because with the inquiry approach students can be more active, and have ideas in solving math problems.